Improvement in Retinal Capillary Rarefaction After Valsartan Treatment in Hypertensive Patients. Issue 11 (16th June 2016) - Jumar, Agnes; Harazny, Joanna M.; Ott, Christian; Kistner, Iris; Friedrich, Stefanie; Schmieder, Roland E.
Abstract : Decreased capillary density influences vascular resistance and perfusion. The authors aimed to investigate the influence of the renin‐angiotensin receptor blocker valsartan on retinal capillary rarefaction in hypertensive patients. Retinal vascular parameters were measured noninvasively and in vivo by scanning laser Doppler flowmetry before and after 4 weeks of treatment with valsartan in 95 patients with hypertension stage 1 or 2 and compared with 55 healthy individuals. Retinal capillary rarefaction was determined with the parameters intercapillary distance (ICD) and capillary area (CapA). In hypertensive patients, ICD decreased (23.4±5.5 μm vs 21.5±5.6 μm, P <.001) and CapA increased (1564±621 vs 1776±795, P =.001) after valsartan treatment compared with baseline. Compared with healthy normotensive controls (ICD 20.2±4.2 μm, CapA 1821±652), untreated hypertensive patients showed greater ICD ( P <.001) and smaller CapA ( P =.019), whereas treated hypertensive patients showed no difference in ICD ( P =.126) and CapA ( P =.728). Therapy with valsartan for 4 weeks diminished capillary rarefaction in hypertensive patients.